SOSIALISASI DAN PENERAPAN BANK SAMPAH DALAM UPAYA PENGELOLAAN SAMPAH RUMAH TANGGA DI RT. 06 KELURAHAN PENURUNAN KOTA BENGKULU - Sari, Aplina Kartika; Gustina, Mely; Saputra, Arie Ikhwan (LPPM Institut Pendidikan Nusantara Global, 2022)
Waste management in the community still uses the waste management paradigm which relies on the final approach (the gathering transport-discard paradigm) which is time to be abandoned and replaced with a new paradigm of processing that relies on reducing waste and handling waste through waste banks. The purpose of this community service is the socialization and establishment of a waste bank in an effort to manage household waste in RT.06 Bengkulu City Reduction Village. The methods used in this community service activity are socialization, technical training, mentoring, and monitoring the evaluation of waste bank activities. This activity is aimed at improving the understanding, knowledge, and skills of RT.06 residents. Kelurahan Penurunan as a partner in implementing the waste bank system. The establishment of this waste bank is an initial momentum in fostering the collective consciousness of the community to start sorting, recycling, and utilizing waste. This is important because waste has a selling point and environmentally sound waste management can become Indonesia's new culture. All activities in the waste bank system are carried out from, by, and for the community. Like conventional banks, waste banks also have a managerial system whose operations are carried out by the community. Waste banks can even provide economic benefits for the community.